Effects of Mongolian Warm Acupuncture on iNOS/NO and Inflammatory Cytokines in the Hippocampus of Chronic Fatigue Rats - Shui, Ling; Yi, Ru-Na; Wu, Yong-Jie; Bai, Shu-Mei; Si, Qin; Bo, A-gula; Wuyun, Ge-Rile; Si, Leng-Ge; Chen, Ying-Song; Lu, Jun (Frontiers in Integrative Neuroscience, 2020)
The inducible nitric oxide synthase/nitric oxide (iNOS/NO) signaling pathway and inflammatory cytokines play important roles in the pathogenesis of exercise-induced fatigue. Studies have found that Mongolian warm acupuncture (WA) could alleviate exercise-induced fatigue. However, the exact mechanisms underlying its effects remain unclear. In the present study, we investigated the effects of Mongolian WA on iNOS/NO signaling pathway and proinflammatory cytokines in a chronic exhaustive swimming induced fatigue rat model. Animals were randomly divided into Control group, Ctrl+WA group, Model group and Model+WA group. The body weight, exhaustive swimming time test, and Morris water maze test were performed before and after the chronic exhaustive swimming. The serum levels of interleukin-1β (IL-1β), interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), interferon-γ (IFN-γ) and iNOS were detected by enzyme linked immunosorbent assay (ELISA). The mRNA expressions of IL-1β, IL-6, TNF-α, IFN-γ and iNOS in the hippocampus were measured by real-time polymerase chain reaction (RT-PCR). Moreover, the protein expression of iNOS in the hippocampus was measured by western-blot and the NO productions in the serum and hippocampus were detected by Griess reaction system. Chronic exhaustive exercise significantly reduced the body weight and exhaustive swimming time, and induced impairment in learning and memory, and which were reversed by WA treatment. Chronic exhaustive exercise also increased the expressions of iNOS and proinflammatory cytokines, while WA treatment significantly decreased the level of iNOS and proinflammatory cytokines. However, chronic exhaustive exercise did not affect the NO production. These findings demonstrated that WA could alleviate the chronic exhaustive swimming-induced fatigue and improve the learning and memory ability, and the actions might be related to the reduction of inflammatory response and iNOS expression.